2021
DOI: 10.3390/ijerph18041734
|View full text |Cite
|
Sign up to set email alerts
|

Food Acquisition and Daily Life for U.S. Families with 4- to 8-Year-Old Children during COVID-19: Findings from a Nationally Representative Survey

Abstract: Evidence of short-term impacts of the coronavirus disease 2019 (COVID-19) pandemic on family life is emerging. Continued research can shed light on potential longer-term impacts. An online survey of U.S. parents with 4- to 8-year-old children (n = 1000) was administered in October 2020. The survey examined parent-reported impacts of COVID-19 on lifestyle (e.g., work, child-care, grocery shopping), as well as current family food acquisition and eating behaviors (e.g., cooking, restaurant use). Descriptive stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 30 publications
1
27
0
1
Order By: Relevance
“…Parents felt it was not as safe or as pleasant to eat out due to the restrictions in place. This corresponds to findings from a US survey (administered in October 2020) of families ( 61 ) reporting that takeaway was perceived as safer (than eating in restaurants), and increased during COVID-19. Takeaway food has been found to be excessive in portion size, energy, macronutrients, and salt ( 66 ).…”
Section: Discussionsupporting
confidence: 81%
“…Parents felt it was not as safe or as pleasant to eat out due to the restrictions in place. This corresponds to findings from a US survey (administered in October 2020) of families ( 61 ) reporting that takeaway was perceived as safer (than eating in restaurants), and increased during COVID-19. Takeaway food has been found to be excessive in portion size, energy, macronutrients, and salt ( 66 ).…”
Section: Discussionsupporting
confidence: 81%
“…As a result, the number of restaurants that purchased local food based on a perspective of sustainability had increased [14]. Another study by Ferrante et al [15] also found changes in the lifestyles of most people as well as in their behaviors regarding acquiring or eating food since the outbreak of the COVID-19 pandemic. The findings showed an increase in not only home cooking and online grocery shopping but also in takeout and delivery.…”
Section: Related Studies 21 Changes In Dining-out Patterns After the Covid-19 Pandemicmentioning
confidence: 99%
“…Snacking appears to have increased among Canadian families, but in some cases, healthier behaviours, such as home cooking, also increased (Carroll et al, 2020 ). A majority of US parents reported doing more home cooking during the pandemic and only a third reported take-out/delivery food consumption, but an alarming two thirds reported food insecurity (Ferrante et al, 2021 ). Increases in food insecurity were associated with greater parental concerns about obesity and about one third of families increased their consumption of high-calorie snack foods, sweets/desserts, and fruits in the home (Adams et al, 2020 ).…”
Section: Eating Habitsmentioning
confidence: 99%
“…L’apport en collations semble avoir augmenté; par contre, certaines habitudes alimentaires plus saines, telle la cuisine maison, ont pris le dessus chez certains (Carroll et al, 2020 ). Aux É-U, la plupart des parents déclarent cuisiner plus souvent pendant la pandémie et seuls un tiers disent consommer des plats à emporter/livraison (Ferrante et al, 2021 ). Par contre, et voici le facteur inquiétant, deux tiers signalent une insécurité alimentaire.…”
Section: Alimentationunclassified